The people who discovered Columbus : the prehistory of the Bahamas - Keegan, William F., 1955- (Columbus quincentenary series., 1992)
For the Lucayan Tainos of the Caribbean, the year 1492 marked the beginning of the end: the first people contacted by Christopher Columbus were the first extinguished. Within thirty years, a population of perhaps 80,000 had declined to, at most, a few refugees. Clearing new ground in the study of prehistoric societies, William Keegan argues that a different perspective on the past provides an accurate portrait of a culture that became extinct almost 500 years ago.